Influence of the bridging atom in fluorene analogue low‐bandgap polymers on photophysical and morphological properties of copper indium sulfide/polymer nanocomposite solar cells. Issue 19 (31st July 2013) - Jäger, Monika; Trattnig, Roman; Postl, Markus; Haas, Wernfried; Kunert, Birgit; Resel, Roland; Hofer, Ferdinand; Klug, Andreas; Trimmel, Gregor; List, Emil J. W.
ABSTRACT This contribution presents the correlation between structural, morphological, and fluorescence properties as well as device performance of nanocomposite solar cells comprising two low‐band gap polymers, poly[[9‐(1‐octylnonyl)−9H‐carbazole‐2, 7‐diyl]‐2, 5‐thiophenediyl‐2, 1, 3‐benzothiadiazole‐4, 7‐diyl‐2, 5‐thiophenediyl] (PCDTBT) and poly[2, 1, 3‐benzothiadiazole‐4, 7‐diyl‐2, 5‐thiophenediyl(9, 9‐dioctyl‐9H‐9‐silafluorene‐2, 7‐diyl)−2, 5‐thiophenediyl] (PSiF‐DBT) and copper indium sulfide (CIS). It shows that, in analogy to organic solar cells, the device efficiency is strongly determined by different polymer structures leading to a different packing of the polymer chains and consequently to diverse morphologies. X‐ray diffraction investigation indicates increased semicrystallinity in PSiF‐DBT compared with the nitrogen analogue PCDTBT. The photoluminescence (PL) quenching of this polymer indicates that the higher photogeneration achieved in PSiF‐DBT based films can be correlated to a favorable donor‐acceptor phase separation. Transmission electron microscopy studies of PCDTBT:CIS blended films suggest the formation of polymer agglomerates in the layer resulting in a decreased PL quenching efficiency. For the considered polymer:CIS system, the combination of these effects leads to an enhanced overall device efficiency. © 2013 Wiley Periodicals, Inc. J. Polym. Sci. Part B: Polym. Phys. 2013, 51, 1400–1410